2013
DOI: 10.1080/09593330.2013.839719
|View full text |Cite
|
Sign up to set email alerts
|

Modelling response patterns of physico-chemical indicators during high-rate composting of green waste for suppression ofPythium ultimum

Abstract: High-rate composting studies on green waste, i.e. banana leaves (BL) and lawn clippings (LC), were conducted in 0.25-m3 rotary barrel composters to evaluate and model changes in key physico-chemical parameters during composting. Time to compost maturity and antagonistic effects and relationships of composts against Pythium ultimum were also investigated. Higher temperatures were achieved in LC compost (LCC), which did not translate to higher total organic carbon (TOC) loss but resulted in lower carbon to nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The composting process can be modeled based on one variable (single regression) model or multiple variables (multiple linear regression (MLR)) model. St Martin et al used different function models to simulate different parameters of the composting process, leading to the recognition that the composting temperature and OC are best described by the critical exponential function and the rectangular hyperbolic function, respectively [53]. ON, C/N, and pH are best described by double Fourier functions, while electrical conductivity (EC) is best described via Fourier functions.…”
Section: Data-driven Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The composting process can be modeled based on one variable (single regression) model or multiple variables (multiple linear regression (MLR)) model. St Martin et al used different function models to simulate different parameters of the composting process, leading to the recognition that the composting temperature and OC are best described by the critical exponential function and the rectangular hyperbolic function, respectively [53]. ON, C/N, and pH are best described by double Fourier functions, while electrical conductivity (EC) is best described via Fourier functions.…”
Section: Data-driven Modelsmentioning
confidence: 99%
“…For the data-driven model, in addition to the conventional sensitivity analysis (n = 7), there is the adopting analysis of variance (ANOVA), which can also be used to achieve the purpose of sensitivity analysis (n = 3) in terms of selected input variables. For instance, the ANOVA of St Martin et al indicated that composting formula, time and composting formula interacting through time had a significant impact on the variables such as temperature, total organic carbon (TOC), total Kjeldahl nitrogen (TKN), C/N, pH, and EC [53]. Li et al showed that the effect of addition ratio and addition time on nitrogen loss was statically significant at the 95% confidential level through ANOVA [54].…”
Section: Sensitivity Analysis and Validationmentioning
confidence: 99%
See 2 more Smart Citations